Selective Deletion of the Mechanistic Target of Rapamycin From the Renal Collecting Duct Principal Cell in Mice Down-Regulates the Epithelial Sodium Channel - Chen, Bruce; Fluitt, Maurice B.; Brown, Aaron L.; Scott, Samantha; Gadicherla, Anirudh; Ecelbarger, Carolyn M. (Frontiers in Physiology, 2022)
The mechanistic target of rapamycin (mTOR), a serine-threonine-specific kinase, is a cellular energy sensor, integrating growth factor and nutrient signaling. In the collecting duct (CD) of the kidney, the epithelial sodium channel (ENaC) essential in the determination of final urine Na+ losses, has been demonstrated to be upregulated by mTOR, using cell culture and mTOR inhibition in ex vivo preparations. We tested whether CD-principal cell (PC) targeted deletion of mTOR using Cre-lox recombination would affect whole-body sodium homeostasis, blood pressure, and ENaC regulation in mice. Male and female CD-PC mTOR knockout (KO) mice and wild-type (WT) littermates (Cre-negative) were generated using aquaporin-2 (AQP2) promoter to drive Cre-recombinase. Under basal conditions, KO mice showed a reduced ( 30%) natriuretic response to benzamil (ENaC) antagonist, suggesting reduced in vivo ENaC activity. WT and KO mice were fed normal sodium (NS, 0.5% Na+) or a very low Na+ (LS, < 0.02%) diet for 7-days. Switching from NS to LS resulted in significantly higher urine sodium losses (relative to WT) in the KO with adaptation occurring by day 2. Blood pressures were modestly ( 5-10 mm Hg) but significantly lower in KO mice under both diets. Western blotting showed KO mice had 20-40% reduced protein levels of all 3 subunits of ENaC under LS or NS diet Immunohistochemistry of kidney showed enhanced apical-versus-cellular localization of all 3 subunits with LS, but a reduction in this ratio for gamma-ENaC in the KO. Furthermore, the KO kidneys showed increased ubiquitination of alpha-ENaC and reduced phosphorylation of the serum and glucocorticoid regulated kinase, type 1 (SGK1) on serine 422 (mTOR phosphorylation site). Taken together this suggests enhanced degradation as a consequence of reduced mTOR kinase activity and downstream upregulation of ubiquitination may have accounted for the reduction at least in alpha-ENaC. Overall, our data support a role for mTOR in ENaC activity likely via regulation of SGK1, ubiquitination, ENaC channel turnover and apical membrane residency. These data support a role for mTOR in the collecting duct in the maintenance of body sodium homeostasis.